A novel molecularly imprinted method with computational simulation for the affinity isolation and knockout of baicalein from Scutellaria baicalensis. (21st July 2015) - Li, Hong; He, Hongliang; Huang, Jiaojiao; Wang, Chong‐Zhi; Gu, Xiaoli; Gao, Yankun; Zhang, Hongjuan; Du, Shuhu; Chen, Lina; Yuan, Chun‐Su
Abstract: A novel molecularly imprinted polymer (MIP) was synthesized by precipitation polymerization with baicalein (BAI) as the template and used as solid‐phase extraction (SPE) adsorbent, aiming at the affinity isolation and selective knockout of BAI from Scutellaria baicalensis Georgi (SB). We used computational simulation to predict the optimal functional monomer, polymerization solvent and molar ratio of template to functional monomer. Characterization and performance tests revealed that MIP exhibited uniform spherical morphology, rapid binding kinetics, and higher adsorption capacity for BAI compared with nonimprinted polymer (NIP). The application of MIP in SPE coupled with high‐performance liquid chromatography to extract BAI from SB showed excellent recovery (94.3%) and purity (97.0%). Not only the single BAI compound, but also the BAI‐removed SB extract was obtained by one‐step process. This new method is useful for isolation and knockout of key bioactive compounds from herbal medicines. Copyright © 2015 John Wiley & Sons, Ltd.